EFEKTIVITAS PELATIHAN SELF-REGULATED LEARNING DALAM MENINGKATKAN PRESTASI MATEMATIKA DI MADRASAH TSANAWIAH “X” SLEMAN - Nadia Yumna; Sukarti Sukarti; Uly Gusniarti (Program Studi Psikologi Universitas Malahayati, 2020)
THE EFFECTIVITY OF SELF-REGULATED LEARNING TRAINING TO INCREASE THE STUDENT’S MATHEMATICS ACHIEVEMENT OF MADRASAH TSANAWIYAH “X” SLEMANThis research aimed to determine the effectivity of Self-Regulated Learning training to increase the student’s mathematics achievement. Subject in this research were 27 student of class VIII MTs